Cooperative gating between ion channels - Choi, Kee-Hyun (GENERAL PHYSIOL AND BIOPHYSICS, 2014)
Cooperative gating between ion channels, i.e. the gating of one channel directly coupled to the gating of neighboring channels, has been observed in diverse channel types at the single-channel level. Positively coupled gating could enhance channel-mediated signaling while negative coupling may effectively reduce channel gating noise. Indeed, the physiological significance of cooperative channel gating in signal transduction has been recognized in several in vivo studies. Moreover, coupled gating of ion channels was reported to be associated with some human disease states. In this review, physiological roles for channel cooperativity and channel clustering observed in vitro and in vivo are introduced, and stimulation-induced channel clustering and direct channel cross linking are suggested as the physical mechanisms of channel assembly. Along with physical clustering, several molecular mechanisms proposed as the molecular basis for functional coupling of neighboring channels are covered: permeant ions as a channel coupling mediator, concerted channel activation through the membrane, and allosteric mechanisms. Also, single-channel analysis methods for cooperative gating such as the binomial analysis, the variance analysis, the conditional dwell time density analysis, and the maximum likelihood fitting analysis are reviewed and discussed.
Keywords: SUPERPOSITION PROPERTIES; ACETYLCHOLINE-RECEPTORS; RELEASE CHANNEL; CA2+; SKELETAL; NOISE; MEMBRANE; CONDUCTANCE; PRECISION; MECHANOSENSITIVITY